FENOMENA EKSPLOITASI LADIES COMPANION (LC) DI THE VENUS KOTA PALEMBANG - Julietha Sabela; Yoyok hendarso; Safira soraida (Jurnal Media Sosiologi (JMS), 2021)
Exploitation of women means the utilization of the everything belonged and inherent in women. One of the main purpose of exploitation of women is to increase the attention and interest of customers according to the expertise possessed by women, just like the exploitation of Ladies Companion. There are several factors that encourage women work There are several factors that make women willing to work as Ladies Companion, one of which is due to economic factors. This research purposes to determine the conditions of exploitation of the Ladies Companion and the background of the exploitation of the Ladies Companion at The Venus, Palembang City by using Max Weber's concepts and theories. The benefits of this research are useful in the development of social sciences, gender sociology, family sociology and as a reference in helping to enrich concepts and contributions.This research method is descriptive qualitative method. The results of this research indicate that the exploitation conditions of the Ladies Companion receive physical and non-physical exploitation of women. In addition, the Ladies Companion must be ready to provide services from ordinary to services outside the karaoke service and cannot refuse it because there is an agreement. The work time what obtained by the Ladies Companion are erratic because they must be ready whenever guests want to book them to accompany karaoke. The background of the exploitation of the Ladies Companion is mainly due to economic factors, social environment, education and low skills. So, willing to work as a Ladies Companion is conducted because of an encouragement and a causal factor.